Sleep quality associated with habitual physical activity level and autonomic nervous system of smokers - Trevisan, Iara Buriola [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP]; Proença, Mahara; Barreira, Tiago V.; Santos, Caroline Pereira [UNESP]; Gouveia, Tamara Santos [UNESP]; Ramos, Ercy Mara Cipulo [UNESP]; Ramos, Dionei [UNESP] (Sociedade Brasileira de Cardiologia, 2021)
Background: Few studies have examined the relationship of one’s habitual physical activity level and autonomic nervous system (ANS) modulation on sleep quality in smokers. Objective: The aim of this study was to identify changes in the sleep quality of smokers and its relation with their habitual physical activity level and ANS modulation. Methods: Forty-two smokers were divided into two groups according to the 50th percentile of the moderate-to-vigorous physical activity (MVPA). Sleep quality was assessed using the Mini-sleep Questionnaire, and ANS modulation was assessed by indices of heart rate variability (HRV). To examine the possible mean differences, the analysis of covariance (ANCOVA) was used, adjusted for age, sex, body composition, pack-years, beta-blockers, anxiety, and depression in log base 10, not including qualitative data, such as sex and beta-blockers. Correlations were made by using the Spearman rank correlation. The statistical significance was set at 5% Results: The smokers who were less active showed poor sleep quality (p=0.048) and insomnia (p=0.045). Furthermore, the less active group presented decreased parasympathetic modulation [HF (un; p=0.049); RMSSD (ms; p=0.047) and SD1 (ms; p=0.047)] and an increased LF (un) index (p=0.033) and LF/HF ratio (p=0.040). A positive correlation between the total Mini-sleep score with LF (un) index (r=0.317, p=0.041) and LF/HF ratio (r=0.318, p=0.040) and negative correlation with HF (un) index (r= -0.322, p=0.038). Conclusions: Smokers with lower levels of habitual physical activity showed poor sleep quality and alterations in autonomic nervous system modulation; (Arq Bras Cardiol. 2021; 116(1):26-35).
Keywords: Autonomic Nervous System Diseases; Exercise. Heart Rate; Quality; Sleep; Tobacco Use Disorder